Content Marketing Optimization to Increase Consumer Engagement at Brand Necerel on Instagram platform - Hisyam, Al Hisyam Nurussyahban; Muhammad, Denlora Nor; Abdurahman, Abdurahman; Setiawan, Risqi Firdaus (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Content Marketing Optimization to Increase Consumer Engagement at Brand Necerel on Instagram Platform. Introduction, Marketing 4.0 provides an important role for marketers to guide the customer journey from the initial stage to the final stage. Content Marketing is a marketing strategy that ensures definite identification with strong analysis to attract the attention of potential customers distributed through digital media. The main purpose of implementing content marketing is to increase customer engagement. Methods: MBKM Independent Internship activities for students of the National Development University “Veteran” East Java at Qurota Academy as Digital Marketers at @Necerel.id began on February 19 - June 19, 2024. Internship activities are carried out face-to-face (Offline) at the Office located at Jalan Selat Karimata Block E3/1, Sawojajar, District. Kedungkandang, Malang City, East Java, 65139. The results of this study help optimize Content Marketing to Increase Consumer Engagement in the Brand Necerel on the Instagram platform.